Intervensi Partai Politik dalam Suksesi Kepemimpinan Muktamar Nahdlatul Ulama ke 33 di Jombang tahun 2015 - Abdul Hakim Syafi'i; Budhi Gunawan; Firman Manan (Universitas Negeri Medan, 2019)
This research aims to find out that there is political party intervention in the 33rd Nahdlatul Ulama Congress (Muktamar NU) in Jombang. This research managed to uncover the fact that political conflict unfolding during the Muktamar has not emerged suddenly, but the accumulation from the diverse antagonistic relation among nahdliyyin’s organizational management. Of course, the main determinant was inextricably linked with political rivalries among NU elite in order to dominate and to influence the NU’s organizational policy according to each interest. In light of the context, therefore, conflict and elite theory analysis are used as analytical lancet so as to find the driving factors in the conflict within the 33rd NU Muktamar leadership succession. This research uses the qualitative method with descriptive research type. Data were collected through observation and interview. Through this research, I intend to give the scientific contribution that can be considered as a reflection matter for NU organization. As a scientific work, this research tries as much as possible to prioritize the objectivity. Through the unfolding dynamic in Muktamar NU in Jombang, I am interested in to scrutinize why political partiy elite involve directly there so it appears that there is political parties intervention to the Muktamar result and I want to find out what factors drove political conflict in the Muktamar.